Chemical bonding analysis on MgEH15 (E = Sc and Y), highly stable clusters for hydrogen storage (2022)
Magnesium based alloys containing scandium and yttrium are promising materials for hydrogen storage devices due to the hydrogen absorption and desorption kinetic and thermodynamic properties, results showing the reversibility of the hydrogenation reaction and leads to a long-lasting energy source. Nevertheless, to the best of our knowledge, there are no theoretical studies comparing the stability between Y and Sc-doped systems available in the literature. In this contribution, we report an analysis of stability and chemical bonding nature for a series of complexes MgEHn (E = Sc and Y, where n = 10 –16) with the aim to understand the nature of binding between a hydrogen molecule and the core system of the metal blend. The results obtained suggest that yttrium-bonded hydrogen molecules are more labile for a dehydrogenation step in comparison to those with scandium. Additionally, based on QTAIM and EDA-NOCV calculations, we conclude that alloys containing scandium are predicted to be more tightly bonded to H2 molecules than those with yttrium. Consequently, the dehydrogenation reaction would be more thermodynamically favorable for the latter